Sinkronisasi Kecerdasan Buatan Dan Manajemen Berbasis Karakter Menuju Indonesia Emas 2045 - Tasnim Sofya Dewi A.S (Universitas Pakuan, 2026)
Synchronizing Artificial Intelligence and Character-Based Management toward Golden Indonesia 2045 This study analyzed the synchronization of artificial intelligence (AI) and character-based management (CBM) in transforming national education governance toward Golden Indonesia 2045. The study responded to the need for greater efficiency, accurate decision-making, and personalized learning without weakening the human values of education. A qualitative literature-review design was employed. Data were drawn from policy documents, academic books, institutional reports, and scientific articles on AI in education, character education, school governance, and digital transformation. The sources were analyzed through data reduction, thematic grouping, cross-source comparison, and conclusion drawing. The findings showed that AI could support administrative automation, adaptive learning, early identification of learning difficulties, and data-informed policy evaluation. CBM was essential for directing technology toward integrity, responsibility, fairness, empathy, and respect for learners’ dignity. Their synchronization required ethical leadership, data protection, teacher capacity building, equitable infrastructure, and meaningful human oversight. Therefore, AI should function as a decision-support instrument, while character values should determine the purpose, limitations, and accountability of its use.